Economic burden of healthcare utilisation by older persons living in the community in Malaysia - Haron, Sharifah Azizah; Koris, Roshanim; Mehmet Orhun, Nimetchan; M Nur, Amrizal; Mohamed Aljunid, Syed; Akmal Shafie, Asrul (Pro Medicina Foundation, 2024)
Objective: The aim of the study is to estimate the economic burden of healthcare utilisation by older persons in Malaysia at a national scale. The specific objectives are to: (1) identify the healthcare utilisation behaviour of older persons; (2) estimate the direct and indirect healthcare costs at the community setting, and (3) estimate the economic burden of healthcare utilisation by older persons.